2016
DOI: 10.1124/mol.116.103267
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Treprostinil for Enhancing Hematopoietic Progenitor Cell Transplantation

Abstract: Activation of Gs-coupled receptors enhances engraftment of hematopoietic stem and progenitor cells (HSPCs). We tested the hypothesis that treprostinil, a prostacyclin analog approved for the treatment of pulmonary hypertension, can be repurposed to improve hematopoietic stem cell transplantation. Murine and human HSPCs were isolated from bone marrow and umbilical cord blood, respectively. Prostanoid receptor agonists and the combination thereof with forskolin were tested for their capacity to stimulate [3H]cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 39 publications
0
29
1
Order By: Relevance
“…CXCR4 is a chemokine receptor whose expression has been shown to increase in response to treprostinil exposure in hematopoietic stem cells (24). CXCR4 message increased slightly, but insignificantly, in uninvolved tissue from treprostinil-treated, naïve mice and urethane-treated mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 is a chemokine receptor whose expression has been shown to increase in response to treprostinil exposure in hematopoietic stem cells (24). CXCR4 message increased slightly, but insignificantly, in uninvolved tissue from treprostinil-treated, naïve mice and urethane-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated CXCR4 expression correlates with aggressive metastasis, advanced stage disease, and shorter overall NSCLC survival rates(35). A recent publication by Kazemi and colleagues demonstrated that treprostinil (and not iloprost or beraprost) increased CXCR4 expression in hematopoetic stem and progenitor cells (HSPC), enhanced CXCR4 mediated HSPC migration, and improved the engraftment of HSPCs in lethally irradiated mice without impairing their self-renewal capacity(24). The enhanced ability of treprostinil to boost CXCR4 related pathway activity may explain its lack of chemopreventive properties.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this dose provided the optimum beneficial effect in promoting hematopoietic stem cell transplantation in lethally irradiated recipient mice [24]. In previous work, we noted a bell-shaped dose-response curve of treprostinil, suggesting that a higher dose of treprostinil is less beneficial than the currently used dose.…”
Section: Discussionmentioning
confidence: 97%
“…Raising cAMP by activation of Gαs enhances engraftment of HSCs [4]. This can be achieved by pretreating HSCs in vitro with prostanoid E and I receptor agonists, e.g., dimethyl-PGE2 (dmPGE2) [5,6] or treprostinil [7]. Treprostinil has two advantages: it is an approved drug and it can also be administered in vivo, which further enhances bone marrow reconstitution in recipient animals [7].…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by pretreating HSCs in vitro with prostanoid E and I receptor agonists, e.g., dimethyl-PGE2 (dmPGE2) [5,6] or treprostinil [7]. Treprostinil has two advantages: it is an approved drug and it can also be administered in vivo, which further enhances bone marrow reconstitution in recipient animals [7]. Similarly, genetic deletion or inhibition of dipeptidyl peptidase-4 (DPP4/CD26) promotes the reconstitution of the bone marrow after HCT [8,9].…”
Section: Introductionmentioning
confidence: 99%